الآيات التي وصفها بعض المفسرين بفصيحات القرآن: دراسة استقرائية مقارنة - العمودي، إيمان بنت عبدالله بن عمر (الأمانة العامة لهيئة كبار العلماء, 2024)
يعنى هذا البحث باستقراء وجمع الآيات التي وصفها بعض المفسرين بفصيحات القرآن، والكشف عن سبب إطلاق هذا الوصف على هذه الآيات خاصة، وما امتازت بها من مزايا، وقد انتظم عقده في مقدمة وتمهيد، وفصلين، وخاتمة على النحو التالي: التمهيد، ثم الفصل الأول: مصطلح فصيحات القرآن، والفصاحة بين كلام العرب وآيات القرآن الكريم، وفيه ثلاثة مباحث: المبحث الأول: التعريف بمصطلح فصيحات القرآن، المبحث الثاني: الفصاحة بين كلام العرب، وآيات القرآن الكريم المبحث الثالث: أبرز المفسرين الذين استعملوا مصطلح فصيحات القرآن. الفصل الثاني: الآيات العشر الموصوفة بفصيحات القرآن، وتحته عشرة مباحث، ثم الخاتمة: وفيها أهم النتائج والتوصيات. وقد سرت في البحث على المنهج الاستقرائي التحليلي المقارن وكان من أهم أهدافه: -جمع الآيات الموصوفة بفصيحات القرآن، وبيان عددها، وإثبات من وصفها بهذا الوصف من أهل التفسير، وعقد المقارنة بين عباراتهم. -الكشف عن سبب وصف هذه الآيات خاصة بـ (فصيحات القرآن)، ومزاياها، مع أن جميع آيات القرآن فصيحة. -وجاءت توصية البحث على النحو التالي: -تتبع المصطلحات الخاصة التي أطلقت على أي من القرآن الكريم عند المفسرين وغيرهم، وإفرادها بالدراسة والمقارنة. -دراسة الفرائد القرآنية اللفظية الموجودة في الآيات الموصوفة بـ: (فصيحات القرآن) دراسة تفسيرية دلالية. This paper undertakes an in-depth examination and compilation of verses characterized by certain commentators as eloquent in the Quran. It seeks to unveil the reasons behind such characterization, particularly the distinctive qualities these verses possess. The research consists of a foreword, introduction, two chapters, and a conclusion, as follows: Introduction and Chapter One: Introduction to the term «eloquence in the Quran." Exploring eloquence in the context of Arabic discourse and Quranic verses. Three sections: Definition of the term "eloquence in the Quran," eloquence in Arabic discourse, and prominent commentators employing the term. Chapter Two: Ten sections addressing the ten verses described as eloquent in the Quran. Conclusion: Key findings and recommendations. The research adopts a comparative analytical and inductive approach, with primary objectives including: Compilation of verses characterized as eloquent in the Quran, determining their number, and who gave the verses that label, among the exegetes, with a comparison of their terms. Explaining the reasons behind the specific characterization of these verses as "eloquent in the Quran" and highlighting their merits, acknowledging the inherent eloquence of all Quranic verses. Recommendations include the following: Exploring and studying the specific terms employed by commentators and others in describing the Quranic verses. Investigating the linguistic benefits found in verses described as "eloquent in the Quran" from an interpretative and semantic perspective
Keywords: البلاغة القرآنية -- فصيحات القرآن -- الآيات القرآنية -- تفسير القرآن